A Transcriptomics Approach to Unveil the Antioxidant Effects of Tryptophan on Oocyte Quality Under Oxidative Stress in Pigs - Zhekun Zhu; Yanlong Li; Xinyin Fan; Shuang Cai; Siyu Li; Yutian Wang; Xinyu Wang; Fengjuan Yang (Biomolecules)
This study investigates the effect of tryptophan treatment on aged pig oocytes, focusing on its potential to reduce oxidative stress and improve oocyte quality. An oxidative stress model was induced using hydrogen peroxide (H2O2) to mimic aging effects on oocytes. Fresh ovaries from young sows were collected, and oocytes were aspirated and cultured for in vitro maturation. Oocytes in the H2O2 and the H2O2+Trp groups were exposed to 100 µM H2O2 for 30 min, with the H2O2+Trp group receiving an additional 50 µM tryptophan supplementation. RNA-sequencing was performed to study the underlying mechanism through which tryptophan mitigated the H2O2-induced oxidative stress in oocytes. The results demonstrated that tryptophan supplementation significantly reduced oxidative stress markers such as H2O2 and malonaldehyde (MDA) while restoring key antioxidant enzymes such as superoxide dismutase (SOD), and catalase (CAT) confirming its antioxidant role. Furthermore, tryptophan improved cumulus cell expansion, and oocyte quality, which were compromised by oxidative stress. Transcriptomics study revealed the enrichment of several KEGG pathways, such as P13K-Akt signaling pathways as a critical regulator of cell survival and function, emphasizing the protective effects of tryptophan on oocyte integrity. Moreover, the protein–protein interaction (PPI) network identified several hub genes in the tryptophan-treated group compared with H2O2, including TIMP1, CCN2, and MMP12 as key players in ECM remodeling and cellular adhesion, which are critical for restoring oocyte quality. These findings suggest that tryptophan supplementation not only mitigated oxidative stress but also modulated gene expression related to cellular functions and stress response. These results propose that tryptophan could be a valuable therapeutic strategy for improving reproductive outcomes in aging sows and other mammals facing age-related oocyte dysfunction.